2012
DOI: 10.1002/jcp.23001
|View full text |Cite
|
Sign up to set email alerts
|

CD73‐generated adenosine promotes osteoblast differentiation

Abstract: CD73 is a GPI-anchored cell surface protein with ecto-5′-nucleotidase enzyme activity that plays a crucial role in adenosine production. While the roles of adenosine receptors (AR) on osteoblasts and osteoclasts have been unveiled to some extent, the roles of CD73 and CD73-generated adenosine in bone tissue are largely unknown. To address this issue, we first analyzed the bone phenotype of CD73-deficient (cd73−/−) mice. The mutant male mice showed osteopenia, with significant decreases of osteoblastic markers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 45 publications
(55 reference statements)
10
84
1
Order By: Relevance
“…To date, strong evidence has implicated A2BR in osteoblast differentiation and function (20,22,(32)(33)(34), but little evidence supports a role for either A1R or A2AR in the regulation of osteoblast differentiation or function. Thus, Gharibi et al (35) reported that, although A1R was expressed in osteoblast precursors, it was involved in induction of adipocyte differentiation rather than osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, strong evidence has implicated A2BR in osteoblast differentiation and function (20,22,(32)(33)(34), but little evidence supports a role for either A1R or A2AR in the regulation of osteoblast differentiation or function. Thus, Gharibi et al (35) reported that, although A1R was expressed in osteoblast precursors, it was involved in induction of adipocyte differentiation rather than osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a synthetic A2B receptor agonist has been shown to increase bone formation, and osteoblasts from A2B receptor knockout mice display reduced activity in vitro (Carroll et al, 2012). Recently, it was reported that the adenosine generated by ecto-5'-nucleotidase (CD-73) was important in promoting osteoblast differentiation (Takedachi et al, 2012). In contrast, adenosine analogues, acting via the A1 or A2A receptors, have been shown to inhibit the differentiation of rodent osteoblast-like cells (Gharibi et al, 2012).…”
Section: P1 Receptor Signalling and Osteoblastsmentioning
confidence: 99%
“…Without these enzymes, bone development fails to progress normally. For example, CD73 knockout mice are osteopenic and have diminished osteoblast function [27].…”
Section: Adenosine Signalingmentioning
confidence: 99%
“…Similarly, Takedachi et al proposed that CD73 promotes osteoblast development through A2BR but not A2AR. Using MC3T3-E1 cells that overexpressed CD73, these researchers showed that treatment with an A2BR antagonist suppressed bone sialoprotein and osteocalcin levels, while this effect was not observed with an A2AR antagonists [27].…”
Section: P1 Receptors: A2brmentioning
confidence: 99%